Desynchronized : The Comovement of Non-Hydrocarbon Business Cycles in the GCC - Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2011)
This paper investigates the empirical characteristics of business cycles and the extent of cyclical comovement in the Gulf Cooperation Council (GCC) countries, using various measures of synchronization for non-hydrocarbon GDP and constituents of aggregate demand during the period 1990-2010. By applying the Christiano-Fitzgerald asymmetric band-pass filter and a mean corrected concordance index, the paper identifies the degree of non-hydrocarbon business cycle synchronization?one of the main prerequisites for countries considering to establish a monetary union. The empirical results show low and heterogeneous synchronization in non-hydrocarbon business cycles across the GCC economies, and a decline in the degree of synchronicity in the 2000s, if Kuwait is excluded from the sample, partly because of divergent fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet